Fuzzy analysis of laterally-loaded pile in layered soil - Anh, Pham Hoang (Vietnam Journal of Mechanics, 2014)
A fuzzy finite-element method for analysis of laterally loaded pile in multi-layer soil with uncertain properties is presented. The finite-element formulation is established using a beam-on-two-parameter foundation model. Uncertainty propagation of the soil parameters to the pile response is evaluated by a perturbation technique. This approach requires a few number of classical finite-element equations to be solved and provides reasonable results. A comparison with vertex method is made in a numerical example.